Huge inelastic current at low temperature in graphene nanoribbons. (29th December 2016) - Li, Bo-Lin; Chen, Ke-Qiu
Abstract: The nonequilibrium Green's function and the generalized lowest-order expansion method with consideration of electron–phonon interactions (EPIs) are used to investigate the spin-dependent electronic transport properties of ferromagnetic zigzag graphene nanoribbons. Results show that the consideration of EPIs will lead to a 4–5 orders of magnitude increase of the current in some bias regions when the spin polarizations of two electrodes are antiparallel. This results in the vanishing of the dual spin filtration effect and a narrowing of the effective bias region of giant magnetoresistance. The increases of the current mainly from the first Born scattering process, and can be described by the Fermi's golden rule, and may be a result of the breaking of the structural symmetry by the introduction of phonons.